2019
DOI: 10.1097/pcc.0000000000001861
|View full text |Cite
|
Sign up to set email alerts
|

Are Pediatric Critical Personnel Satisfied With Their Lives? Prediction of Satisfaction With Life From Burnout, Posttraumatic Stress, and Posttraumatic Growth, and Comparison With Noncritical Pediatric Staff

Abstract: Objectives: Staff in PICUs shows high burnout, posttraumatic stress disorder symptoms, and posttraumatic growth levels. However, their levels of satisfaction with life and how positive and negative posttrauma outcomes relate to each other and contribute to predict satisfaction with life remain unknown. Thus, we attempted to explore these aspects and to compare the findings with data from pediatric professionals working in noncritical units. Design: This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 37 publications
0
25
0
1
Order By: Relevance
“…Both Salmon and Morehead’s (2019) study and Vahedian-Azimi et al’s (2019) study reported that ICU nurses with PTSD can experience diminished concentration and cognitive ability, which has been linked to medication errors (Park & Kim, 2013). Hyperarousal symptoms, such as feeling irritable or having angry outbursts, were endorsed by those ICU nurses with high scores measuring PTSD in Rodríguez-Rey et al’s (2019) study.…”
Section: Defining Attributesmentioning
confidence: 61%
See 1 more Smart Citation
“…Both Salmon and Morehead’s (2019) study and Vahedian-Azimi et al’s (2019) study reported that ICU nurses with PTSD can experience diminished concentration and cognitive ability, which has been linked to medication errors (Park & Kim, 2013). Hyperarousal symptoms, such as feeling irritable or having angry outbursts, were endorsed by those ICU nurses with high scores measuring PTSD in Rodríguez-Rey et al’s (2019) study.…”
Section: Defining Attributesmentioning
confidence: 61%
“…In addition, nurses may exhibit a lack of empathy toward their patients, sometimes termed compassion fatigue (Salmon & Morehead, 2019). Many ICU nurses with PTSD experience symptoms of burnout caused by excessive stress in the demanding work environment (Colville et al, 2017; Mealer et al, 2009; Rodríguez-Rey et al, 2019). Burnout arises from the inability to cope with work-related stress over an extended period of time and is characterized by emotional exhaustion, depersonalization (cynical or indifferent attitude toward one’s job), and decreased sense of personal accomplishment (Maslach et al, 1986; Vahedian-Azimi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Exploring these changes may help them reflect on their experience and find meaning in it, which may mitigate the negative effect of traumatic work-related experiences and improve their satisfaction with life. 14 The PTG model proposed by Tedeschi and Calhoun 15 suggests that rumination is an important cognitive process that leads to individual growth through traumatic events or negative changes. However, previous studies have mainly focused on the negative emotions of frontline nurses.…”
Section: Introductionmentioning
confidence: 99%
“…However, participating mothers also had relatively high levels of education and income, which matched the control group well. Furthermore, many of the members of the control group work in a high-stress hospital environment, which is prone to burnout, 42 making the identified differences between mothers and controls all the more striking. If compared to women from the general population, differences in health-related quality of life and emotional distress may have been even larger.…”
Section: Discussionmentioning
confidence: 99%